Examen Especial a los Ingresos y Gastos de Gestión de la Empresa Pública Municipal Mercado de Productores Agrícolas “San Pedro de Riobamba” Periodo 2020. - Chavez Ticse, Jessica Morelia (2022)
The following research topic was carried out with the aim of performing a Special Examination of the income and management expenses of the Public – Municipal Agricultural Producers´ Market Company “San Pedro de Riobamba” year 2020. The one that was executed during the 2022 period, with the implementation of techniques and instruments such as interviews and surveys, It began with phase one “planning”, that allowed to obtain general information, as well as financial information to be evaluated during the execution process; on the other hand, in the execution phase, programs are carried out for each of the components, both for income and expenses, where an analysis of balances of the most representative values of budget is conducted, and finally, in the results´ communication phase, a report reading letter is made, as well as the general “Special Examination report”, which details the conclusions and recommendations to both the Highest Authority and the Financial Directorate. For this reason during the process of the Special Examination, non-compliance with budget execution was detected, both in income and expenses, furthermore a need for training of the personnel of the Financial Department was required, as well as the lack of personnel purely for internal control since, due to its nature, the company should have an area specifically for this activity.